Aetiology, Clinical Profile and Outcome of Acute Kidney Disease in Children Presenting in a Tertiary Health Institution in Southwest, Nigeria - Ajite, A. B.; Ogundare, E. O.; Subulade, A. A.; Adebisi, A. O. (British Journal of Healthcare and Medical Research, 2025)
Acute kidney injury (AKI) in children is a disease entity resulting from acute insult to both kidneys leading to reduced glomerular filtration rate, impairment of fluid and electrolyte homeostasis in the body, and accumulation of waste product of metabolism. It is a recognized cause of morbidity and mortality in children. Aim: This study aims to detect the risk factors and prevailing causes of AKI in children presenting at a tertiary hospital in South West Nigeria, identify the various intervention/treatment modalities and determine the predictors of disease outcome. Methods: A retrospective cross-sectional study of children presenting in both the children’s emergency unit and children’s outpatient clinic of Ekiti State University Teaching Hospital Ado Ekiti, Nigeria with AKI over five years September 2019-September 2024. AKI was defined by reduction in urine output (<0.5mls/kg/hour for older children and urine output of< 1ml/kg /hour in infants) of more than 6hours duration and/or increased serum creatinine of either ≥ 0.3mg/dL or a percentage increase of ≥ 1.5 times baseline. Results: A total of 55 children with a diagnosis of acute kidney injury were seen over a period of 5 years. Twenty-nine (52.7%) of them were male with male to female ratio of 1.1:1. The age range was 1 month to 18 years. AKI was seen more in preschool-aged children of less than 3years (32.7%), severe dehydration and sepsis were majorly implicated while AKI secondary to haemoglobinuria was more prevalent among school-aged children. Forty-six (83.6%) children presented with oliguric AKI. Thirty-five (63.6%) children with AKI were conservatively managed, haemodialysis was done in 12(21.8%) patients while peritoneal dialysis was done in 3(5.5%) patients. The mortality was 16.4% (9patients). Statistically significant factors that contributed to the outcome included the age of the patients (p=0.046), the aetiology of AKI (p=0.038), and modality of treatment intervention (p=0.010). Conclusion: Sepsis, severe dehydration and haemoglobinuria were major risk factors for AKI in this study especially in younger children. Primordial prevention of risk factors for AKI and being proactive may stop the progression to acute tubular necrosis and the need for renal replacement therapy.